2005
DOI: 10.2169/internalmedicine.44.542
|View full text |Cite
|
Sign up to set email alerts
|

Association between C-reactive Protein and Insulin Resistance in a Japanese Population: The Minoh Study

Abstract: Objective To investigate the association between Creactive protein (CRP) and insulin resistance.Materials and Methods This study included 1,624 Japanese participants (652 men and 972 women) aged 40 to 69 years who were non-diabetics or did not have medication for hypertension or dyslipidemia, a history of cardiovascular disease or CRP levels >10 mg/l. Serum CRP level, fasting glucose level, and fasting insulin level were measured, and the degree of insulin resistance was assessed using the homeostasis model as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 39 publications
3
30
0
3
Order By: Relevance
“…As in other studies that document the presence of chronic mild inflammation in obesity 30 and metabolic syndrome 31 , adults with MetS showed increased C-reactive protein and lower albumin serum levels than the control group members. In the MetS group, the increased serum CRP levels are due to higher levels of proinflammatory chemokines and cytokines, which are related to systemic and vascular low-grade inflammation and associated with abdominal obesity.…”
Section: Discussionsupporting
confidence: 77%
“…As in other studies that document the presence of chronic mild inflammation in obesity 30 and metabolic syndrome 31 , adults with MetS showed increased C-reactive protein and lower albumin serum levels than the control group members. In the MetS group, the increased serum CRP levels are due to higher levels of proinflammatory chemokines and cytokines, which are related to systemic and vascular low-grade inflammation and associated with abdominal obesity.…”
Section: Discussionsupporting
confidence: 77%
“…Some studies have suggested a possible role of subclinical inflammation in insulin resistance and glucose intolerance that only partly explained the link between obesity and impaired glucose homeostasis (32 ). It has also been documented that chronic, subclinical inflammation, as indicated by increased circulating CRP concentrations, is more strongly associated with postchallenge glycemia than with fasting glucose in nondiabetic adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, CRP showed significant reduction compared to pre-treatment, which might be attributed to the association between CRP with insulin resistance [35,36] and adipocyte excess [37] supporting the effect of diet and weight loss on insulin resistance and consequently hyperandrogenism. The current experiment is limited to the mentioned diet therapy protocol, it's also limited to 12 weeks and 24 weeks measuring intervals, and to the exact measured dermatological, biochemical, and anthropometric parameters that were gathered.…”
Section: Discussionmentioning
confidence: 87%